Chemical equilibria : exact equations and spreadsheet programs to solve them - Pardue, Harry L. (Boca Raton : CRC Press, Taylor & Francis Group, 2019)
Concepts, procedures and programs described in this book make it possible for readers to solve both simple and complex equilibria problems quickly and easily and to visualize results in both numerical and graphical forms. They allow the user to calculate concentrations of reactants and products for both simple and complicated situations. The user can spend less time doing calculations and more time thinking about what the results mean in terms of a larger problem in which she or he may be interested.
Effects ionic strength -- Monoprotic acid-base equilibria; exact and approximate options -- Concepts and equations relevant to a systematic approach to acid-base equilibria -- A systematic approach to monoprotic acid-base equilibria without and with correction for ionic strength -- A systematic approach to monoprotic, diprotic and polyprotic acid-base equilibria -- Some applications of acid-base equilibria -- Solubility equilibria -- Overview and symbols for complex ion reactions and equilibria -- Equilibrium calculations for multistep complex- formation reactions -- Equilibrium calculations for metal-ion/EDTA reactions.
OCLC-licensed vendor bibliographic record.
Keywords: Chemical equilibrium; Chemical equilibrium -- Mathematics; Acid-base equilibrium; Neutralization (Chemistry); SCIENCE / Chemistry / Physical & Theoretical; SCIENCE / Chemistry / General; SCIENCE / Chemistry / Analytic; SCIENCE / Chemistry / Industrial & Technical